Competitive contact in the future - Grig, Rufus (Henry Stewart Talks, 2009)
What is changing and why, From transaction to value, Obsession with call duration, SLAs and other targets, Call routing, Scripting, Business trends, Technology within the contact center, Convergence, Web 2.0
Archived at 2025/05/28